Teaching Community College Students Strategies for Learning Unknown Words as They Read Expository Text - Leslie Craigo; Linnea C. Ehri; Manijeh Hart (Laureate Education Inc, 2017)
An experiment was conducted to investigate methods that enable college students to learn the meaning of unknown words as they read discipline-specific academic text. Forty-one college students read specific passages aloud during three sessions. Participants were randomly assigned to three vocabulary learning interventions or a control condition. The interventions involved applying context, morphemic, and syntactic strategies; applying definitions; or applying both strategies and definitions to determine word meanings. Word learning and comprehension were measured during the interventions and in a transfer task to assess treatment effects on independent text reading. Results revealed that students in all three intervention groups outperformed controls in learning words and comprehending passages. However, the treatment groups did not differ from controls on the transfer task. Teaching both strategies and definitions was especially effective for learning unknown words and comprehending text containing those words.